2012
DOI: 10.1371/journal.pone.0049401
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for the Identification of Targets Specific to Bone Metastasis Using Cancer Genes Interactome and Gene Ontology Analysis

Abstract: Metastasis is one of the most enigmatic aspects of cancer pathogenesis and is a major cause of cancer-associated mortality. Secondary bone cancer (SBC) is a complex disease caused by metastasis of tumor cells from their primary site and is characterized by intricate interplay of molecular interactions. Identification of targets for multifactorial diseases such as SBC, the most frequent complication of breast and prostate cancers, is a challenge. Towards achieving our aim of identification of targets specific t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…We found that a gene signature consisting of 273 genes important for breast cancer bone metastasis showed decreased expression in ABL1/ABL2 knockdown cells (Fig. 6B) (38). Further, inactivation of the ABL kinases resulted in decreased expression of the genes in the Hippo, JAK/STAT, and Cytokine/Cytokine Receptor pathway signatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that a gene signature consisting of 273 genes important for breast cancer bone metastasis showed decreased expression in ABL1/ABL2 knockdown cells (Fig. 6B) (38). Further, inactivation of the ABL kinases resulted in decreased expression of the genes in the Hippo, JAK/STAT, and Cytokine/Cytokine Receptor pathway signatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from such studies have added to the information as well as to the noise. Lately, the focus has been towards creating systems biological molecular interactome models of complex diseases using these data [2][3][4][5][6][7]. This endeavour has been supported by methodologies such as data mining, Natural Language Processing (NLP), crowd sourcing and graph theory [2,3,16].…”
Section: Control Mechanisms Of Complex Diseases Using Systems Biologimentioning
confidence: 99%
“…However, contrary to expectations, reductionist investigations of complex diseases have led to increase in noise making it difficult to ascertain specific causative molecular mechanisms that could be used to control the disease [1]. Hence prompted by increasing need of integrating disparate molecular elements, systems biological strategies have been developed to create a holistic picture of molecular mechanisms underlying complex diseases [2][3][4][5][6][7]. These integrative models allow one to wade through the noise and to pin down specific targets and regulatory mechanisms, thus providing a rational strategy towards disease control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone metastasis is a complex process that involves a series of molecular events involving multiple steps, factors and genes [5]. First, tumor cells separate from the primary tumor origin and then intrude into the circulatory system through newly formed tumor vessels.…”
Section: Introductionmentioning
confidence: 99%